Popular punishment: on the normative significance of public opinion - Ryberg, Jesper; Roberts, Julian V. (Studies in penal theory and philosophy, 2014)
What role should public opinion play in the way the state deals with criminal offenders? This volume brings together leading philosophers, legal theorists, and criminologists to consider the various aspects of the relationship between public opinion and state punishment.